Ecohydrological effects of water reservoirs with consideration of asynchronous and synchronous concurrences of high- and low-flow regimes. Issue 4 (12th March 2018) - Zhang, Zhenghao; Zhang, Qiang; Singh, Vijay P.; Peng, Sun
ABSTRACT: Inflow of nine reservoirs in the Liao River basin, China, is used to analyse the concurrence of high/low flows, and also the ecological instream flow. The results indicate that the general extreme value distribution model performs well in describing the probabilistic behaviour of high/low flows in the basin. Specifically, the Gumbel and Frank copula functions perform better than other functions. Reservoir inflow encounter series are subject to high synchronous concurrence, at greater than 27% for low flow vs low flow. Thus, the water supply system of the basin is not steady. The ecological instream flow can be analysed by a monthly frequency computation method, with 90% guarantee rate. The low-flow periods are January, February and May, and water transfers are not feasible in these periods. Thus, external sources of water are urgently needed to guarantee sufficient water supply to provide critical water resources and to protect important aquatic environments.